The Warrior’s Gift of Death: Magic Realism in Avanti Popolo - Ne’eman, Judd; Munk, Yael (MiKAN, 2026)
The essay offers a new reading of Rafi Boukai’s classic Israeli film Avanti Popolo (1986). Boukai’s feature, it claims, draws on the ending of an earlier Israeli film set during the Six Day War, Uri Zohar’s Every Bastard Is a King (1968), two of whose minor characters become the protagonists of Avanti Popolo. Employing Jameson’s theory of magic realism and Deleuze and Guattari’s concept of deterritorialization, the essay analyzes the film’s antiwar stance as expressed from the perspective of enemies building a relationship based on human solidarity. This stance is also examined in light of Boukai’s speech at the Montpellier Film Festival in France, where the director expressed his radical opposition to the 1982 Lebanon War, a conflict fifteen years removed from the events of Avanti Popolo